The C57BL/6N mouse substrain is a viable model of elastase-induced abdominal aortic aneurysm - Wei, Panpan; Li, Kexin; Li, Meng; Liu, Haole; Xia, Congcong; Chen, Yajie; Zhao, Sihai; Li, Yankui (Frontiers in Cardiovascular Medicine, 2024)
Aim Compared with the C57BL/6N substrain, the C57BL/6J substrain is more susceptible to the angiotensin II (Ang II)-induced development of dissected abdominal aortic aneurysms (AAAs). The aim of this study was to elucidate whether the widely used C57BL/6N mouse substrain is as susceptible as the C57BL/6J mouse substrain to porcine pancreatic elastase (PPE) infusion-induced experimental nondissected AAA development. Methods Experimental nondissected AAAs were induced in C57BL/6J and C57BL/6N mice via transient aortic luminal infusion of PPE. On Day 0 (baseline) and Day 14 after PPE infusion, the abdominal aortic diameter was directly measured. Aortic aneurysmal segment samples were collected, and histopathological analysis was performed. Results On Day 14 after PPE infusion, aortic diameters were significantly increased in both mouse substrains (from approximately 0.51 to 1.24 mm in C57BL/6J mice and from 0.51 to 1.18 mm in C57BL/6N mice). The increase in diameter of all the mice exceeded 50% and met the criteria for AAA model establishment (143% and 135% in C57BL/6J mice and C57BL/6N mice, respectively). PPE infusion also induced obvious local aortic wall macrophage and T-cell infiltration, elastin degradation, smooth muscle cell depletion and high metallopeptidase (MMP)-2 and MMP-9 expression levels in C57BL/6N mice, but these differences were not significant compared with those in C57BL/6J mice. However, PPE infusion led to the recruitment of more B cells and the sprouting of more neovessels at the aneurysmal lesion site in C57BL/6J mice than in C57BL/6N mice. Conclusion The C57BL/6N mouse substrain is suitable for establishing a model of AAA via elastase infusion.